Performance of altitude acclimatized and non-acclimatized professional football (soccer) players at 3,600 m - Brutsaert, T. D.; Spielvogel, H.; Soria, R.; Araoz, M.; Caceres, E.; Buzenet, G.; Villena, M.; Pazzamora, M.; Vargas, E. (Journal of Exercise Physiology online, 2000)
European football (soccer) matches frequently are played at the international level in mountainous regions of South America. In this study, the exercise response during cycle ergometry and the rate of football match energy expenditure (RFE) were measured in two groups of professional football players at high altitude (3,600 m) and near sea level (420 m). Subjects either resided at high altitude and were therefore altitude acclimatized (n= 9) (HA), or resided near sea level and were non-acclimatized to high altitude (n=11) (LA). Both study groups showed a large decrement in the RFE (0.187 kcal/kg/min, or a 16% decrease) and peak oxygen consumption (VO2peak) at altitude (10.78 mL/kg/min for HA and 6.27 mL/kg/min for LA). This VO2peak decrement with altitude was larger in LA versus HA players (20% vs. 13%). The LA players also showed higher ventilatory equivalents for oxygen, lower arterial oxygen saturations, and higher arterial lactate concentrations during submaximal exercise. Because aerobic capacity is an important determinant of football match performance, these results may have some relevance to the debate over an advantage to altitude acclimatized teams for football matches played at moderate to high altitude.